ANALISIS PEMBERIAN SUAKA TERHADAP AHMED CHATAEV OLEH AUSTRIA DITINJAU DARI SUDUT PANDANG HUKUM PENGUNGSI INTERNASIONAL - Fauzie Nur Ramadhan (BELLI AC PACIS (Jurnal Hukum Internasional), 2024)
This study examines the granting of asylum to Ahmed Chataev by Austria from the standpoint of international refugees. This research is a normative legal research viewed from prescriptive and uses several approaches, namely a legal approach, a conceptual approach, and a case approach. The research uses primary and secondary law material. The data was collected by library research and analyzed by deductive method with syllogism.  The results of this study indicates  that Ahmed Chataev acquired the asylum from Austria and the status as a refugee he owned legitimately, as in article 1 letter A paragraph (2) of the Convention of Geneva 1951. The application for extradition from Russia was rejected by Ukraine and Bulgaria due to the status of Ahmed Chataev as refugees as well as concerns for the safety of his life.